1997
DOI: 10.12693/aphyspola.91.405
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Magnetic Studies of New Mixed-Valence Compounds: K3Cu8Se6, KCu3Se2, K3Cu8Te6and BaCuS3-x

Abstract: New mixed-valent copper chalcogenides BaCuS3_ x and K3Cu8X6 with X = Se or Te and KCu3Se2, with chemical patterns corresponding to the recently investigated K3Cu8S6 and KCu3S2, were synthesized. For these new samples the results of resistivity and magnetic susceptibility measurements are presented. For BaCuS 3 _x , K3Cu8Se6 and KCu3Se2 the metal-insulator transition is observed with the low temperature phase being metallic, which is untypical, whereas K3Cu8Te6 is a metal in the investigated temperature range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Jacyna-Onyszkiewicz et al , briefly reported the temperature-dependent resistivity of KCu 3– x Se 2 and observed an interesting transition from semiconducting to metallic behavior at ∼160 K. However, the resistivity data contained several erratic steps, and their reproducibility was not discussed. The contact material in that case was not specified, but we observed similar irregular, nonreproducible behavior when Ag paste contacts were used on KCu 3– x Se 2 single crystals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jacyna-Onyszkiewicz et al , briefly reported the temperature-dependent resistivity of KCu 3– x Se 2 and observed an interesting transition from semiconducting to metallic behavior at ∼160 K. However, the resistivity data contained several erratic steps, and their reproducibility was not discussed. The contact material in that case was not specified, but we observed similar irregular, nonreproducible behavior when Ag paste contacts were used on KCu 3– x Se 2 single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Although its crystal structure was unknown, Jacyna-Onyszkiewicz et al briefly reported its temperature-dependent resistivity. 23,24 These data contained unexplained anomalies that bore resemblance to charge-density-wave formation (e.g., as in TiSe 2 25 ) and thus warranted further study. Here we present the synthesis, crystal structure, and optical and electronic properties of KCu 3−x Se 2 .…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meanwhile, the chalcogenidometalates with a mixed valence have received considerable attention due to their unique properties and promising applications in superconductivity, metallic conductivity, charge-density waves, and magnetism . However, hitherto the mixed-valent chalcogenidostannates­(II,IV) have rarely been isolated.…”
mentioning
confidence: 99%